Enabling technology for the creation and sharing of knowledge - Abu Bakar, Ahmad Zaki (2001)
What are the enabling technologies for the creation and sharing of knowledge? Before we embark to discuss the technology element of a knowledge management system, we must first address the more fundamental issues, such as why organizations need to create and share knowledge and is information technology a critical component in this endeavour? Although the need for a knowledge management system is clear, most organizations have not found a good-fit technology solution. The reason is because technology is an enabler for knowledge management. A more important key success factor is a well-defined and aligned knowledge management strategy. Besides giving an overview of the current strategy and approaches, this paper also looks at the knowledge management system architectures and the differences between a Western and an Eastern knowledge management system architecture.